Perencanaan Komunikasi Kesehatan Untuk Mencegah Kanker Serviks Perempuan di Puskesmas Tanjung Morawa Kab. Deli Serdang - Rieska Fauzianti Noor; Nina Siti Salmaniah Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study explores how Puskesmas communication planning plays a role in the success of the cervical cancer prevention program in Tanjung Morawa. The research method used was qualitative with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction techniques, data presentation, and verification or conclusion drawing. The results of this study indicate that the health communication planning carried out by the Tanjung Morawa Health Center to prevent the dangers of cervical cancer are: (1) Problem analysis. Puskesmas Tanjung Morawa visited every posyandu in the hamlets. (2) Audience planning and formulating communication objectives, Puskesmas Tanjung Morawa targets the community, especially women in Tanjung Morawa. (3) Planning media or communication channels, Puskesmas Tanjung Morawa collaborates with the PKK Tanjung Morawa District, village midwives, clinics in the Tanjung Morawa working area, and Lonsum to disseminate information on efforts to prevent the dangers of cervical cancer by making socialization and using social media such as Instagram. (4) Message development planning, in the distribution of messages, the Tanjung Morawa Health Center shares messages that are persuasive and informative. (5) Evaluation of health communication planning carried out by Puskesmas Tanjung Morawa.